Setting the table for rural food access - Abigail Darwin; Nicole Nunoo; Jung Lee; Abigail Borron; Jennifer Thompson (Journal of Agriculture, Food Systems, and Community Development)
The Southeastern United States was built upon agriculture, but paradoxically its rural residents experience high rates of food insecurity due to numerous intersecting socio-economic barriers. Food insecurity leads to higher rates of diet-related chronic disease in rural populations compared to their urban counterparts, further compounded by limited access to healthcare. Guided by the theoretical frameworks of assets-based community development and the culture-centered approach, this paper investigates existing program models that guide the establishment of community-derived programs to increase the availability and accessibility of locally sourced fruit and vegetables for low-income residents of the rural Southeast. Data were collected through document analysis and semi-structured interviews with leadership from twelve community-derived food access programs in Appalachia and the Deep South. Using a framework approach, data were analyzed to identify and characterize current models based on their structures and guiding values. Four program models were identified: the Charity Model, the Support Model, the Restructure Model, and the Market Model, which range from providing emergency food to restructuring the local food system. We present characteristics of each model, the challenges faced, and lessons learned by participating programs. In addition to identifying the four models, an unexpected result of this work was uncovering subtle yet important differences between Appalachian and Deep South programs that reflect their divergent, yet parallel cultural histories of marginalization and resilience.